Analysis Analysis of Leading Sectors in Binjai City Using the Location Quotient (LQ) And Shift Share Method - Siburian, Rowinna; Angela Anggraini; Muammar Rinaldi (Outline Publisher, 2025)
This article analyzes the leading sectors of Binjai City using the Location Quotient (LQ) method based on Gross Regional Domestic Product (GRDP) data from 2019 to 2023. Secondary data was collected from the Central Statistics Agency (BPS) using a quantitative approach. The results of the analysis show that sectors with an LQ value above 1 have the potential to become the basis of the economy, especially the Mining and Quarrying sector which will reach an LQ of 2.45 in 2023. A focus on development on leading sectors such as Mining, Education Services and Accommodation Provision is needed to encourage sustainable economic growth . The analysis also indicates a positive contribution from specialized sectors with a stable National Growth Component (KPN) value of 0.31, where the agriculture, forestry, fisheries and wholesale and retail trade sectors show significant growth.